Ինքնուսուցման կարողությունների ձևավորման համակարգը - Մանուկյան, Անի (Զանգակ հրատ.)
Learning to learn, one of the eight competences that EU has defined, comprises the disposition and ability to organize and regulate one’s own learning, both individually and in groups. Learning to learn includes the ability to manage one’s time effectively, to solve problems, to acquire, process, evaluate and assimilate new knowledge, and to apply new knowledge and skills in a variety of contexts — at home, at work, in education and in training. In more general terms, learning-tolearn contributes strongly to managing one’s own career path. Although ‘learning to learn’ should be an important part of daily life in secondary schools and classrooms, it turns out to be a very difficult goal to achieve. For most schools and for most teachers it is not even clear how ‘learning to learn’ should be operationalized and implemented. Умение учиться является одной из восьми компетенций, выделенных ЕС, которая включает в себя мотивацию и способность организовывать и регулировать собственное обучение как индивидуально, так и в группах. Это умение включает в себя способность эффективно управлять своим временем, решать проблемы, приобретать, обрабатывать, оценивать и усваивать новые знания, а также применять новые знания и навыки в различных ситуациях - дома, на работе, в учебных заведениях и в процессе обучения. В более широком смысле умение учиться оказывает большое влияние на процесс управления собственной карьерой. “Умение учиться” должно стать важной частью повседневной жизни в особенности у учащихся средних школ. Однако достичь этой цели оказывается очень сложно. Для большинства школьных учителей остается неясным, как “умение учиться” должно быть активизировано и реализовано.
Keywords: Ուսուցման և դասավանդման մեթոդիկա